Analisis Beban Kalor Pada Ruang Laboratorium Desain Dan Konstruksi Jurusan Teknik Mesin Fakultas Teknik Universitas Halu Oleo - Sisa, Arsin; Balaka, Ridway; Sudia, Budiman (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2023)
Air refresher is a process of cooling the air so that it can reach the appropriate temperature and humidity required for the air condition of a certain room. The purpose of this study is to calculate the heat load in the design and construction laboratory of the mechanical engineering department, Faculty of Engineering, Halu Oleo University. The method used in this study is an analytical method by calculating the cooling load on each predetermined parameter, namely on walls, roofs, windows, doors, as well as lighting, electronic equipment and occupants. This calculation is carried out every hour from 08.00 to 17.00 local time. The results showed that the cooling load increased significantly from 08.00 until the peak occurred at 13.00 to 14.00, then the cooling load began to decrease significantly at 15.00 to 17.00. The high cooling load that occurs at 13.00 and 14.00 is thought to be due to the sun's rays coming at a vertical angle so that the heat received is greater than in the afternoon or evening where the angle of incidence of the sun's rays is tilted.Keywords: Air refresh, Cooling load